Predictors of incident and recurrent participation in the sale or delivery of drugs for profit amongst young methamphetamine users in Chiang Mai Province, Thailand, 2005-2006 - Amanda D. Latimore (2018)
Background: Despite Thailand's war on drugs, methamphetamine (" yaba" in Thai) use and the drug economy both thrive. This analysis identifies predictors of incident and recurrent involvement in the sale or delivery of drugs for profit amongst young Thai yaba users. Methods: Between April 2005 and June 2006, 983 yaba users, ages 18-25, were enrolled in a randomized behavioural intervention in Chiang Mai Province (415 index and 568 of their drug network members). Questionnaires administered at baseline, 3-, 6-, 9-, and 12-month follow-up visits assessed socio-demographic factors, current and prior drug use, social network characteristics, sexual risk behaviours and drug use norms. Exposures were lagged by three months (prior visit). Outcomes included incident and recurrent drug economy involvement. Generalized linear mixed models were fit using GLIMMIX (SASv9.1). Results: Incident drug economy involvement was predicted by yaba use frequency (adjusted odds ratio [AOR]: 1.05; 95% confidence interval [CI]: 1.01, 1.10), recent incarceration (AOR: 2.37; 95% CI: 1.07, 5.25) and the proportion of yaba-using networks who quit recently (AOR: .34; 95% CI: .15, .78). Recurrent drug economy involvement was predicted by age (AOR: 0.81; 95% CI: 0.68, 0.96), frequency of yaba use (AOR: 1.06; 95% CI: 1.02, 1.09), drug economy involvement at the previous visit (AOR: 2.61; CI: 1.59, 4.28), incarceration in the prior three months (AOR: 2.29; 95% CI: 1.07, 4.86), and the proportion of yaba-users in his/her network who quit recently (AOR: .38; 95% CI: .20, .71). Conclusion: Individual drug use, drug use in social networks and recent incarceration were predictors of incident and recurrent involvement in the drug economy. These results suggest that interrupting drug use and/or minimizing the influence of drug-using networks may help prevent further involvement in the drug economy. The emergence of recent incarceration as a predictor for both models highlights the need for more appropriate drug rehabilitation programmes and demonstrates that continued criminalization of drug users may fuel Thailand's yaba epidemic. © 2011 Elsevier B.V.